Investigating Language in the Machine Translation: Exploring Yoruba- English Machine Translation as a Case Study (2014)
Computer now translates human language without having any machine translation understanding of it. How does this happen? The answer to the language acquisition question is the concern of this paper. This paper opines that even language and though machine could only count and match for translation, the deficiencies seen in its translation are not majorly computer's rather the exploration of language acquisition. The paper explores two opposing views on language acquisition and used them to explain the processes of machine translation using Google translator and Ibadan on-going SMT research as example. It concludes that when human can adequately explain human language acquisition then there could be answer to modeling machine to master human language for translation.